An apple in one hand, a gun in the other: Public support for arming our nation's schools - Jonson, Cheryl Lero (Criminology & public policy, 2021)
Research summary In the wake of repeated school shootings, today's youth have acquired the label of the “mass shooting generation.” Another fitting label would be the “armed school generation.” Most states now permit school security officers to carry firearms, and at least 466 school districts in 19 states allow teachers or staff members to be armed. In this context, understanding public opinion about guns in schools is essential. Using a 2018 national survey of 1,100 American adults, we examined public support for arming our nation's schools. Although consensus exists for school resource officers carrying weapons, respondents are divided about arming teachers and nonteaching staff. Those who believe in gun defensive effectiveness, lean right politically, are racially resentful, older, and have children are more likely to endorse arming nonlaw enforcement school personnel. National Rifle Association membership and altruistic fear are associated with support for arming teachers, while a belief in the moral wrongness of harming others predicts opposition to teachers having a gun in one hand and an apple in the other. Policy implications The controversy around arming teachers will likely be ongoing. With decisions made locally, public opinion will continue to play an influential role in this debate. Our study provides important new evidence about the extent and correlates of public opinion on guns in schools. The next step is to examine how public attitudes change in response to information about the policy issues associated with arming schools. Future polls should examine the impact being armed has on the teaching profession and localized variations in support for arming the school.